A Preliminary Study of the Association between SOX17 Gene Variants and Intracranial Aneurysms Using Exome Sequencing - Park, Jeong Jin; Kim, Bong Jun; Youn, Dong Hyuk; Choi, Hyuk Jai; Jeon, Jin Pyeong (Journal of Korean Neurosurgical Society, 2020)
Conflicting results regarding SOX17 genes and the risk of intracranial aneurysms (IA) exist in the Korean population, although significant positive correlations were noted in genome-wide association studies in European and Japanese populations. Therefore, we aimed to investigate an association between SOX17 gene variants and IA using exome sequencing data. This study included 26 age-gender matched IA patients and 26 control subjects. The SOX17 gene variants identified from whole-exome sequencing data were examined. Genetic associations to estimate odds ratio (OR) and 95% confidence interval (CI) were performed using the software EPACTS. The mean age of the IA and control groups were 51.0±9.3 years and 49.4±14.3 years, respectively (p=0.623). Seven variants of SOX17, including six single nucleotide polymorphisms and one insertion and deletion, were observed. Among these variants, rs12544958 (A>G) showed the most association with IA, but the association was not statistically significant (OR, 1.97; 95% CI, 0.81-4.74; p=0.125). Minor allele frequencies of the IA patients and controls were 0.788 and 0.653, respectively. None of the remaining variants were significantly associated with IA formation. No significant association between SOX17 gene variants and IA were noted in the Korean population. A large-scale exome sequencing study is necessary to investigate any Korean-specific genetic susceptibility to IA.